Site fidelity, survival and conservation options for the threatened flapper skate (Dipturus cf. intermedia). Issue 1 (13th June 2014) - Neat, Francis; Pinto, Cecilia; Burrett, Ian; Cowie, Lewis; Travis, Justin; Thorburn, James; Gibb, Fiona; Wright, Peter J.
Abstract In order to evaluate if marine protected areas (MPAs) can be expected to confer conservation benefits to large, mobile marine species it is important to assess their site fidelity and habitat ranging patterns. The flapper skate (Dipterus cf. intermedia) is a large, threatened elasmobranch for which MPAs are being considered on the west coast of Scotland. To inform MPA establishment, a multiannual mark–recapture programme, a year‐long static array acoustic study and an archival tagging study of flapper skate were undertaken. Capture–mark–recapture (CMR) modelling of 280 individuals indicated significant heterogeneity in the recapture rate suggesting the region contained a mixture of site‐attached (resident) and vagrant (transient) individuals. The analysis estimated that 100–400 resident individuals were present in the study area. The number of transient individuals was estimated at around 25% of all those tagged. The average annual survival probability of resident individuals was estimated to be 0.64. The acoustic study of 20 individuals demonstrated that over half were resident on a day‐by‐day basis for months at a time. Three individuals were detected over the entire year. Two individuals moved away immediately after tagging and over half moved out of the study area in the springtime. Three data storage tags revealed that resident individuals utilized most of the available depth habitat (6–205 m) in the area and occasionally visited deeper areas outside the immediate study area. The results indicate that the establishment of a MPA would confer conservation benefits to flapper skate in the area. Management should consider all depths in the study area, areas beyond the study site, and alternative conservation measures such as technical gear measures for fisheries. This study has implications for the conservation and management of similar long‐lived, mobile marine species. © 2014 Crown copyright. Aquatic Conservation: Marine and Freshwater Ecosystems © 2014 John Wiley & Sons, Ltd.